Motion Artifact Removal Techniques for Wearable EEG and PPG Sensor Systems - Seok, Dongyeol; Lee, Sanghyun; Kim, Minjae; Cho, Jaeouk; Kim, Chul (Frontiers in Electronics, 2021)
Removal of motion artifacts is a critical challenge, especially in wearable electroencephalography (EEG) and photoplethysmography (PPG) devices that are exposed to daily movements. Recently, the significance of the motion artifact removal techniques has increased since EEG based brain-computer interfaces (BCI) and daily healthcare usage of wearable PPG devices were spotlighted. In this paper, the development on EEG and PPG sensor systems is introduced. Then, understanding of motion artifact and its reduction methods implemented by hardware and/or software fashions are reviewed. Various electrode types, analog readout circuits and signal processing techniques are studied for EEG motion artifact removal. In addition, recent in-ear EEG techniques with motion artifact reduction are also introduced. Furthermore, techniques compensating independent/dependent motion artifacts are presented for PPG.